Developing Scientific Research Competence Of History Teachers Based On Eastern Thinkers' Ideas On Education - Bobonorov Khusan Tolibjonovich (Next Scientists International Journal EIJP, 2026)
This article explores the views of Eastern thinkers on education and upbringing, their role in developing research competence in modern history teachers, and the methodological foundations of this process. The scientific heritage of scholars such as Ibn Sina, Al-Bukhari, Al-Farabi, Beruni, and Amir Temur is integrated with modern pedagogical competencies. The study identifies criteria, methods, and pedagogical conditions for developing research competence in history teachers. Consequently, it provides scientific evidence that an approach based on the heritage of Eastern scholars can effectively enhance the research skills of history teachers.